2011
DOI: 10.1051/0004-6361/201117473
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundance analysis of the open clusters Berkeley 32, NGC 752, Hyades, and Praesepe

Abstract: Context. Open clusters are ideal test particles for studying the chemical evolution of the Galactic disc. However, the number and accuracy of existing high-resolution abundance determinations, not only of [Fe/H], but also of other key elements, remains largely insufficient. Aims. We attempt to increase the number of Galactic open clusters that have high quality abundance determinations, and to gather all the literature determinations published so far. Methods. Using high-resolution (R ∼ 30 000), high-quality (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
140
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 201 publications
24
140
5
Order By: Relevance
“…We present here a comparison of our results with selected previous analyses of Hyades stars: Paulson et al (2003), Schuler et al (2006) and Carrera & Pancino (2011). These works were chosen because they have a larger number of stars in common with our analysis.…”
Section: Comparison With Other Workmentioning
confidence: 82%
See 2 more Smart Citations
“…We present here a comparison of our results with selected previous analyses of Hyades stars: Paulson et al (2003), Schuler et al (2006) and Carrera & Pancino (2011). These works were chosen because they have a larger number of stars in common with our analysis.…”
Section: Comparison With Other Workmentioning
confidence: 82%
“…Spectroscopic studies of FGK-type dwarfs in the Hyades find a metallicity of about +0.13 dex (Cayrel et al 1985;Boesgaard & Friel 1990;Paulson et al 2003;Schuler et al 2006). Regarding the giants, the metallicity values range from +0.10 up to +0.20 dex, where this scatter is usually attributed to the star HIP 20455, a spectroscopic binary (Schuler et al 2006;Carrera & Pancino 2011).…”
Section: Hyades: the Benchmark Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies for similar populations of stars measure slightly steeper slopes of −0.295 ± 0.005 dex kpc −1 (Chen et al 2003), −0.23 ± 0.04 dex kpc −1 (Bartašiūtė et al 2003), and −0.29 ± 0.06 dex kpc −1 (Marsakov & Borkova 2006). However, other studies of open clusters have found little evidence for a vertical gradient (Carrera & Pancino 2011;Jacobson et al 2011a). One potential explanation for the discrepancy is that previous studies did not take into account the radial gradient when measuring the vertical gradient (Carrera & Pancino 2011).…”
Section: Vertical Metallicity Gradientmentioning
confidence: 86%
“…Various tracers have been used including Cepheid variables (e.g., Lemasle et al 2013), planetary nebulae (e.g., Henry et al 2010;Stanghellini & Haywood 2010), H ii regions (e.g., Balser et al 2011), open clusters (e.g., Carrera & Pancino 2011;Frinchaboy et al 2013), B stars (e.g., Daflon & Cunha 2004;Daflon et al 2009), and surveys of main sequence stars (e.g., Cheng et al 2012b for the Sloan Extension for Galactic Understanding and Exploration (SEGUE; Yanny et al 2009) of the Sloan Digital Sky Survey (SDSS; York 2000); Nordström et al 2004 for the GenevaCopenhagen Survey (GCS; Boeche et al 2013) for the Radial Velocity Experiment (Steinmetz et al 2006)). Near the solar circle, the measured amplitude of the Milky Way radial gradient ranges from −0.04 dex kpc −1 in [S/H] in OB stars (Daflon et al 2009) to −0.099 dex kpc −1 in [Fe/H] in main sequence stars between 4 < Gyr < 6 from the GCS (Nordström et al 2004).…”
Section: Introductionmentioning
confidence: 99%